Race, Poverty, and Exclusionary School Security: An Empirical Analysis of U.S. Elementary, Middle, and High Schools. (October 2014) - Kupchik, Aaron; Ward, Geoff
As violence and crime within and around U.S. schools has drawn increased attention to school security, police, surveillance cameras, and other measures have grown commonplace at public schools. Social scientists commonly voice concern that exclusionary security measures are most common in schools attended by poor and non-White students, yet there is little empirical basis for assessing the extent of differential exposure, as we lack research on how exclusionary measures are distributed relative to school and student characteristics. To address this gap in the research, we use nationally representative school-level data from the School Survey on Crime and Safety to consider the security measures employed in elementary, middle, and high schools. Results indicate that while security measures are ubiquitous in U.S. high schools, those considered more exclusionary are concentrated in elementary, middle, and high schools attended by non-White and/or poorer students.